PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK DI SDN 2 RAGAWACANA TAHUN AJARAN 2019/2020 - Hermawan, Iwan (Jurnal Sains Indonesia, 2022)
This School Action Research is entitled “Improving Teacher Performance in Classroom Learning Through Periodic Collaborative Educational Supervision at SDN 2 Ragawacana for the 2019/2020 Academic Year”. The aim is to describe the steps of periodic collaborative educational supervision in carrying out learning, assessing learning achievement, in carrying out follow-up assessments of student learning achievement and in preparing lesson plans and knowing the benefits of periodic collaborative educational supervision in improving student learning outcomes and increasing insight and teacher performance. This research method is school action research which is carried out in 2 cycles of improvement. The subjects of this study were civil servant teachers at SDN 2 Ragawacana, totaling 6 people consisting of 4 female teachers and 2 male teachers. Data collection techniques in this study were carried out through activities in the form of: (a) action planning; (b) implementation of actions; (c) action observation; and (d) reflection. The results showed that the teacher's performance increased in making lesson plans, implementing learning, assessing student achievement as well as in carrying out the follow-up to the results of the student achievement assessment, which was marked by an increase in the average percentage of success in the learning process at the planning stage from 71.98% in cycle 1 to 92.44% in cycle 2. The percentage of the implementation stage of learning from 72.44 in cycle 1 to 93.81 in cycle 2. The learning assessment stage increased from 81.3% in cycle 1 to 90.56% in cycle 2 and Activities follow-up increased from 59.76% in cycle 1 to 83% in cycle 2. Teacher performance increased in developing learning programs, implementing learning, assessing learning achievement, and implementing follow-up on student achievement results. So it can be concluded that the use of the collaborative educative supervision method periodically can improve teacher performance in learning in the class of SDN 2 Ragawacana, Kramatmulya District